2020
DOI: 10.3390/ijms21134812
|View full text |Cite
|
Sign up to set email alerts
|

Steroids and Alzheimer’s Disease: Changes Associated with Pathology and Therapeutic Potential

Abstract: Alzheimer’s disease (AD) is a multifactorial age-related neurodegenerative disease that today has no effective treatment to prevent or slow its progression. Neuroactive steroids, including neurosteroids and sex steroids, have attracted attention as potential suitable candidates to alleviate AD pathology. Accumulating evidence shows that they exhibit pleiotropic neuroprotective properties that are relevant for AD. This review focuses on the relationship between selected neuroactive steroids and the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 167 publications
0
28
0
Order By: Relevance
“…Decreased levels of neurosteroids were observed in AD brains [ 150 , 151 , 152 ]. In particular, the levels of the neurosteroids pregnenolone sulfate (PREGS) and dehydroepiandrosterone sulfate (DHEAS) were significantly reduced in the striatum, hypothalamus and cerebellum of AD patients compared to non-demented controls (postmortem analysis) [ 150 ].…”
Section: New Insight On the Impact Of Abnormal Tau On Neurosteroidmentioning
confidence: 99%
“…Decreased levels of neurosteroids were observed in AD brains [ 150 , 151 , 152 ]. In particular, the levels of the neurosteroids pregnenolone sulfate (PREGS) and dehydroepiandrosterone sulfate (DHEAS) were significantly reduced in the striatum, hypothalamus and cerebellum of AD patients compared to non-demented controls (postmortem analysis) [ 150 ].…”
Section: New Insight On the Impact Of Abnormal Tau On Neurosteroidmentioning
confidence: 99%
“…We found cyclin, that controls the modulation of neurotransmitter, steriod, and cell cycle related pathways are enriched in genes from subgroup 1, subgroup 2, and subgroup 3, respectively. Previous research has shown the dysregulation of cyclin and steroid is related to AD 66,67 . The re-entry of cell cycle in neuronal cell could be the cause of AD 68 .…”
Section: Personalized Drug Repurposing For Alzheimer's Diseasementioning
confidence: 98%
“…Different lines of evidence showed that AD can significantly alter neurosteroidogenesis [ 12 ] and substantial changes in their levels have been observed in the AD brain. As summarized in [ 12 , 80 ], allopregnanolone was found to be significantly decreased in the prefrontal and temporal cortices of AD patients [ 81 - 83 ]. A general trend toward decreased levels of progesterone was observed in all AD patients' brain regions (frontal cortex, striatum, hypothalamus and hippocampus) compared with controls [ 84 ].…”
Section: Steroid Hormones and Neuroinflammation: Biological Mechanisms In Pathological Conditions (Alzheimer’s Disease)mentioning
confidence: 99%
“…Interestingly, DHEAS or estrogens administration was shown to improve cognitive performance in different AD animal models [ 12 ]. Changes in sex steroid levels are also relevant to AD [ 80 ]. Women with AD aged 80 years and older exhibited significantly lower brain 17β-estradiol than age-matched nondemented controls [ 90 , 91 ].…”
Section: Steroid Hormones and Neuroinflammation: Biological Mechanisms In Pathological Conditions (Alzheimer’s Disease)mentioning
confidence: 99%